A Longitudinal Investigation of Task Characteristics Relationships - Griffin, Ricky W. (Academy of Management Journal, 1981)
This study investigated the stability of individual perceptions of task characteristics and the stability of individual reactions to these perceptions at two points in time. Results indicated that individual perceptions of task characteristics are relatively stable over a 3-month time interval. However, individual reactions to perceived task characteristics are less stable and somewhat more complex.